Epistaxis: An Uncommon Presentation of Factitious Disorder (Jalalabad Medical Journal, 2026)
Factitious disorder with physical symptoms is a psychiatric disorder in which an individual deceives others by appearing sick, purposely getting sick or self-injuring. This was a case report of a 22-year-old married woman who was referred to us with a history of headache, nasal bleeding and unconsciousness as a primary clinical manifestation of a factitious disorder, which was diagnosed and treated after further investigation and psychiatric consultation. In this case report, the purpose was to raise the issue of psychiatric problems and their importance alongside physical problems, especially epistaxis.Jalalabad Med J 2025; 22 (1): 40-42.